(untitled) (مجلة إحالات, 2026)
The article analyzes an extracted dialogue passage from the novel “Memory of the Body” by Ahlam Mostaganmi, located at the beginning of the third chapter of the novel and extending over eleven pages. The analysis is based on two principles: The first is the openness of the novel’s text to multiple readings due to its structural characteristic, and the second is the importance of the dialog and its writing methods in revealing the artistic value and symbolic depth of the novel. Our main objective was to highlight the significant value of the passage and the manifestations of creativity and transgression in it through three stages, starting from the structure of the dialog and its connotations, then its contents and the most important semantic dimensions inherent in it, up to the language of the dialog and its issues.